KARAKTERISTIK PETERNAK SAPI DI KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Seba, Isti; Ririmase, Pieter M.; Tomatala, George S. J. (MARSEGU : Jurnal Sains dan Teknologi, 2025)
This study aims to analyze the social, economic, and technical characteristics of cattle farmers in Salahutu District, Central Maluku Regency. The research was conducted in May–June 2025, involving 30 respondents selected through purposive sampling from three villages: Suli, Tulehu, and Liang. Data were collected through observation, structured interviews using questionnaires, and documentation, and then analyzed descriptively using frequency distribution and percentages. The results showed that most farmers were in productive age with considerable farming experience, although their formal education level was relatively low. Cattle farming was still small-scale, with an average ownership of 8.33 heads per farmer, limited land use, and feed sources mainly from local forages and grazing lands. The main challenges faced by farmers included limited capital, seasonal feed availability, and restricted market access. Nevertheless, the high demand for beef offers significant opportunities for developing cattle farming in the region. This study is expected to serve as a reference for policymaking in improving cattle productivity and farmers’ welfare.